Modelagem do crescimento e da produção de Tectona grandis Linn. f. até a idade de rotação - Chaves, Arthur Guilherme Schirmbeck (2013)
In this work, was studied the growth and production of Teak to the rotation age. Stands analyzed were implanted in the 70's, in the city of Indiavaí-MT, an initial density of 2500 trees per hectare. Thinnings were performed in six different periods and intensities, and harvests were conducted in 2010 and 2012. Information was collected on six permanent plots of one thousand square meters, from 23 to 33 years old, to study productivity in a period prior to harvest. And to analyze the growth rates of implantation until the time of harvesting, 32 dominant trees were felled for stem analysis. Were tested several models for represent the volume, the hypsometric equation, the growth and the production. From the growth models selected, were estimated growth curves for diameter, height and volume. The Teak, in the age of 33, reached an average height of 25.00 meters, a diameter (DAP) of 39.75 cm and an average volume of 1.63 cubic meters per tree. Was also carried out the classification of the local productive capacity based on the dominant height. Production was estimated for three site classes, and the settlements studied were classified as class II. This class represents a remaining volume of 237 m3 ha-1 at age 33. The settlement analyzed reached high growth rates when compared to most of Teak plantations in Mato Grosso and the World, but lower than the potential yield achieved in the best sites. The initial density reduction associated with better management strategies may favor the productivity of Teak.